The Transformation of Artificial Intelligence Technology by Developing Managerial Strategies for Student Communication Behavior in Achieving Sustainability - Nengah Sukendri; I Komang Widya Purnama Yasa; I Wayan Astraguna; Ni Putu Ade Resmayani (International Journal of Applied Business and International Management, 2026)
Addressing the transformation of Artificial Intelligence (AI) technology requires a systemic and comprehensive strategy to ensure sustainability. This study aims to examine and analyze the use of AI and management strategies to support the sustainability of students’ communication behavior within non-formal education, particularly in English language course institutions in Mataram City. A quantitative design was employed using a questionnaire, with classical assumption tests, multiple regression analysis, and the coefficient of determination (R²) analyses were conducted in SPSS version 25. The results are interpreted with reference to Technology Adoption Theory, Management Function Theory, and Symbolic Interaction Theory. The findings indicate that AI technology transformation has a significant, positive effect on students’ communication behavior (t-value critical t; 6.463 2.002). Managerial strategy shows no significant effect (t-value critical t; ?0.532 2.040). However, AI technology transformation and managerial strategy jointly have a significant effect on students’ communication behavior in non-formal educational institutions in Mataram City (F-statistic critical F; 24.026 2.901). These results support utilizing AI technology as a driving force, alongside managerial reform, to achieve sustainability in students’ communication behavior. Educators and administrators should be prepared to teach and implement AI in education management to enhance effectiveness and efficiency.